MVP-OWL: a multi-viewpoints ontology language for the Semantic Web. (7th November 2011) - Hemam, Mounir; Boufa?da, Zizette
Domain ontologies are intended to provide a commonly shared understanding among several user communities. Concepts and their relationships are used to explicitly model the real-world phenomena that are of interest to users of specific domain. In practice, a set of a specific-domain applications use different representations of the same real-world entity due to various viewpoints, context and specific interest. In this paper, we are interested in the problem of representing an ontology in heterogeneous organisation by taking into account different viewpoints and different terminologies of various users, groups or even communities in the organisation. Such ontology, called Multi-Viewpoints Ontology, allows heterogeneity and consensus in a heterogeneous organisation. So, our goal is to propose a Multi-Viewpoints Ontology Web Language, which is an extension of OWL-DL language, to allow the multi-viewpoints ontologies representation for the Semantic Web.